Pâté, confit, rillette : recipes from the craft of charcuterie - Polcyn, Brian; Ruhlman, Michael, 1963- (W.W. Norton & Company, 2019)
In Pâté, Confit, Rillette, Brian Polcyn and Michael Ruhlman provide a comprehensive guide to the most elegant and accessible branch of the charcuterie tradition. There is arguably nothing richer and more flavorful than a slice of pâté de foie gras, especially when it<U+2019>s spread onto crusty bread. Anyone lucky enough to have been treated to a duck confit, poached and preserved in its own fat, or a pâté en croute, knows they<U+2019>re impossible to resist. And yet, pâtés, confits, rillettes, and similar dishes featured in this book were developed in the pursuit of frugality. Butchers who didn<U+2019>t want to waste a single piece of the animals they slaughtered could use these dishes to serve and preserve them. In so doing, they founded a tradition of culinary alchemy that transformed lowly cuts of meat into culinary gold. Polcyn and Ruhlman begin with crucial instructions about how to control temperature and select your ingredients to ensure success, and quickly move on to master recipes, offering the fundamental ratios of fat, meat, and seasoning, which will allow chefs to easily make their own variations. The recipes that follow span traditional dishes and modern inventions, featuring a succulent chicken terrine embedded with sautéed mushrooms and flecked with bright green herbs; modern rillettes of shredded salmon and whitefish; classic confits of duck and goose; and a vegetarian layered potato terrine.